Dispositional Drinking Motives: Associations with Appraised Alcohol Effects and Alcohol Consumption in an Ecological Momentary Assessment Investigation - Piasecki, Thomas M. (Psychol Assess, 2013)
Alcohol use can be understood as a strategic behavior, such that people choose to drink based on the anticipated affective changes produced by drinking relative to those produced by alternative behaviors. This study investigated whether people who report drinking for specific reasons via the Drinking Motives Questionnaire-Revised (DMQ-R, Cooper, 1994) actually experience the alcohol effects they purportedly seek. As a secondary goal, we examined relations between drinking motives and indices of the amount of alcohol consumed. Data were drawn from 3,272 drinking episodes logged by 393 community-recruited drinkers during a 21-day Ecological Momentary Assessment investigation. After accounting for selected covariates, DMQ-R enhancement motives uniquely predicted real-time reports of enhanced drinking pleasure. DMQR coping motives were associated with reports of increased drinking-contingent relief and punishment. Enhancement motives uniquely predicted consuming more drinks per episode and higher peak intra-episode estimated blood alcohol concentration. The findings extend the evidence for the validity of the DMQ-R motive scores by demonstrating that internal drinking motives (enhancement and coping) are related to the experienced outcomes of drinking in the manner anticipated by theory.